Sipha maydis sensitivity to defences of Lolium multiflorum and its endophytic fungus Epichloë occultans - Bastías, Daniel A. (2019)
Fil: Bastías, Daniel A. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas Vinculadas a la Agricultura (IFEVA). Buenos Aires, Argentina.